2022
DOI: 10.1097/sap.0000000000002830
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Trends in Medicare Reimbursement and Utilization for Breast Reconstruction

Abstract: PurposeDevelopment of appropriate reimbursement models for breast reconstruction in the United States requires an understanding of relevant economic trends. The purpose of this study is to evaluate longitudinal patterns in Medicare reimbursement for frequently performed breast reconstruction procedures between 2000 and 2019.MethodsReimbursement data for 15 commonly performed breast reconstruction procedures were analyzed using the Centers for Medicare & Medicaid Services Physician Fee Schedule Look-Up Tool for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We initially hypothesized that decreasing Medicare reimbursement rates may be a potential driving force for changes in hospital charges, as studies in various surgical specialties have demonstrated a decline in Medicare reimbursement rates. 7 8 9 13 25 26 However, we found that reimbursements minimally changed over the study period, while hospital charges continued to rise rapidly at a rate faster than the overall Medicare Part B (+29.5% for mastectomy and breast reconstruction CPT codes vs. +11.6% for all CPT codes). One potential contributing factor to excess charges may include the significance of mastectomies and PMBRs in the surgeon's practice.…”
Section: Discussionmentioning
confidence: 77%
“…We initially hypothesized that decreasing Medicare reimbursement rates may be a potential driving force for changes in hospital charges, as studies in various surgical specialties have demonstrated a decline in Medicare reimbursement rates. 7 8 9 13 25 26 However, we found that reimbursements minimally changed over the study period, while hospital charges continued to rise rapidly at a rate faster than the overall Medicare Part B (+29.5% for mastectomy and breast reconstruction CPT codes vs. +11.6% for all CPT codes). One potential contributing factor to excess charges may include the significance of mastectomies and PMBRs in the surgeon's practice.…”
Section: Discussionmentioning
confidence: 77%
“…We initially hypothesized that decreasing Medicare reimbursement rates may be a potential driving force for changes in hospital charges, as studies in various surgical specialties have demonstrated a decline in Medicare reimbursement rates. [7][8][9]13,25,26 However, we found that reimbursements minimally changed over the study period, while hospital charges continued to rise rapidly at a rate faster than the overall Medicare Part B (+29.5% for mastectomy and breast reconstruction CPT codes vs. +11.6% for all CPT codes). One potential contributing factor to excess charges may include the significance of mastectomies and PMBRs in the surgeon's practice.…”
Section: Accepted Manuscriptmentioning
confidence: 72%
“…The authors observed a specialty-wide undervaluation from 2010 to 2020, in line with prior studies on Medicare reimbursement for plastic and reconstructive surgery. [2][3][4] Undervaluation affected microsurgery (−19.2%) and craniofacial surgery (−17.6%) the most, whereas hand surgery (-9.1%) and breast surgery (-6.9%) were the least impacted. The authors' findings serve as a call to action for the Centers for Medicare & Medicaid Services (CMS) to improve its reimbursement methodologies.…”
mentioning
confidence: 99%
“…The authors observed a specialty-wide undervaluation from 2010 to 2020, in line with prior studies on Medicare reimbursement for plastic and reconstructive surgery. 2–4…”
mentioning
confidence: 99%